Prevalence and Risk Factors of Musculoskeletal Complaints Among Clinical Healthcare Workers: Prevalensi dan Faktor Risiko Keluhan Muskuloskeletal di Kalangan Pekerja Kesehatan Klinis - Mohamad A. Akber (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigated the prevalence and risk factors of musculoskeletal complaints among health workers in clinical wards, examining the relationship between these complaints and various work-related and personal variables. Conducted between December 2022 and April 2023, this descriptive study utilized a non-probability, voluntary sample of 100 health workers. Results indicated that 26% of participants reported lower back pain, 49% arm or neck complaints, 44% regular back pain, and 51% leg complaints. Key risk factors included extended work hours without breaks (67%), time pressure (33%), lifting (45%), and stooping (54%). Despite high medium-risk exposure (85%), no participants reported high-risk levels. This study highlights the significant burden of WMSDs among clinical healthcare workers and underscores the need for interventions to reduce duce these risks and improve occupational health. Highlight: Prevalence: A significant portion of healthcare workers reported musculoskeletal complaints, with 51% experiencing leg pain and 49% arm or neck pain. Risk Factors: Key risk factors identified include prolonged work hours without breaks (67%), time pressure (33%), lifting (45%), and stooping (54%). Implications: The study underscores the need for targeted interventions to mitigate WMSDs and improve the occupational health of clinical healthcare workers. Keywords: Musculoskeletal Disorders, Healthcare Workers, Risk Factors, Occupational Health, Clinical Wards